Rheological properties of dough made from wheat-wholegrain buckwheat flour supplemented with herbal mixture Vitaplant® - Nikolić Nada; Sakač Marijana; Mastilović Jasna (Journal on Processing and Energy in Agriculture, 2010)
The importance of wholegrain buckwheat flour is that it is a gluten free food and it is abundant in nutrients, such as proteins, essential amino acids, dietary fibers, starch, vitamins and minerals. Addition of aromatic and spice plants improves the nutritional and health potential of food, improves taste and odor and prevents its deterioration. As rheological properties have great relevance in predicting the final product quality, the effect of Vitaplant® herbal mixture addition on dough rheological properties was studied. The dough was made with wheat- wholegrain buckwheat flour mixture (70:30 w/w) and 2, 3, 5 and 7% of Vitaplant®, where the amount of wheat flour was reduced for the Vitaplant® portion. The addition of herbal mixture Vitaplant® changes the rheological properties of dough. Based on cluster analysis and Euclidean distances, in order to achieve better functional properties of food products, Vitaplant® is recommended in portion of 7%.